DAMPAK COVID-19 TERHADAP EKONOMI PERIKANAN BUDIDAYA DI KOTA LUBUKLINGGAU, SUMATERA SELATAN - La Ode Wahidin; Rudiansyah Rudiansyah; Neksidin Neksidin; Sri Murtini (Jurnal Perikanan Darat dan Pesisir (JPDP), 2020)
Fishery activities especially inland fishery is highly affected by community purchasing power. This interaction is seemly looked clearly due to fish becomes one of daily main protein of people. Happening the pandemic of Covid-19 starts in the middle March 2020 in Indonesia directly affects the social activities of people. This research was aimed at analysing the economic impacts resulted in by the Covid-19 pandemic on inland fishery aquaculture in Lubuklinggau City. Data were gathered on September to October 2020 using interviews. Respondents in this research were defined purposively consisting of fish pond owners and aquaculture practitioners of three main fish commodity in this city such as tilapia, carp, and catfish. The gathered data were qualitatively analysed to confirm descriptively the real condition in this city. The results of this study indicate that the inland fish production in the city during the Covid-19 pandemic is till normal. However, the fish commodity demands experience decrease significantly both fresh and life fish. This decreasing demands directly influence the selling price of fish in the fishermen level. The main causes of this event due to the elimination of crowded social activities like an activity gathered mass and face-to-face education activities. A decrease of selling price, in 18% of the Covid-19 on the normal prices before the pandemic happening, is burdensome highly on the aquaculture fishermen in Lubuklingau City. The lower peak of this decreasing price occurred on September 2020 and this condition would be still taken place until the end of this year. The proper policy is needed in order to maintain the aquaculture activities in this city going forward.